2021
DOI: 10.1002/rra.3880
|View full text |Cite
|
Sign up to set email alerts
|

Spatial characteristics and influencing factors of Chinese traditional villages in eight provinces the Yellow River flows through

Abstract: Along with global urbanization and the dominant trend toward urban‐based policies, traditional villages are facing imbalanced development and the fate of revitalization or decline. In this study, 1,222 Chinese traditional villages in eight provinces the Yellow River flows through have been selected as the typical physical bearers of Chinese civilization of an investigation into the multi‐scale spatial characteristics, and multiple influencing factors and mechanisms for regional patterns and spatial differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…The study found that most of these traditional villages have signi cant characteristics of adjacent paddy elds (Fig. 9), and their inhabitants still maintain the traditional rice farming mode of "rice-sh symbiosis" and "rice-duck symbiosis", which enables them to achieve the purpose of "one land with two uses, one water with two uses, and double or multiple harvests in one season" [97], and the yields are greatly improved, such as the This is the case of the "traditional rice, sh and duck symbiotic agricultural production model -rice, sh and duck system in Congjiang Dong Township, Guizhou", which has supported the villagers to live and work happily for generations and to spread their branches [57], fully re ecting the special function of rice elds to carry traditional civilization continuously; it is estimated that the nearest distance of traditional villages from the 10,000 mu farmland It is estimated that the nearest distance of traditional villages from the 10,000 mu farmland is at least 6 km, and the larger distance is tens to hundreds of kilometers, which has the spatial attribute of being far from the high quality arable land resources such as the mountain at cultivated land, especially the 10,000 mu farmland.…”
Section: Spatial Distribution Of Traditional Villages In Different Hu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that most of these traditional villages have signi cant characteristics of adjacent paddy elds (Fig. 9), and their inhabitants still maintain the traditional rice farming mode of "rice-sh symbiosis" and "rice-duck symbiosis", which enables them to achieve the purpose of "one land with two uses, one water with two uses, and double or multiple harvests in one season" [97], and the yields are greatly improved, such as the This is the case of the "traditional rice, sh and duck symbiotic agricultural production model -rice, sh and duck system in Congjiang Dong Township, Guizhou", which has supported the villagers to live and work happily for generations and to spread their branches [57], fully re ecting the special function of rice elds to carry traditional civilization continuously; it is estimated that the nearest distance of traditional villages from the 10,000 mu farmland It is estimated that the nearest distance of traditional villages from the 10,000 mu farmland is at least 6 km, and the larger distance is tens to hundreds of kilometers, which has the spatial attribute of being far from the high quality arable land resources such as the mountain at cultivated land, especially the 10,000 mu farmland.…”
Section: Spatial Distribution Of Traditional Villages In Different Hu...mentioning
confidence: 99%
“…In addition, domestic scholars have also conducted national-scale research on traditional villages through GIS, geostatistics, and other technical methods: the selected traditional villages in the early stage were mainly concentrated in areas with high economic level, good transportation conditions, and small proportion of minority population [52], and there was a spatial difference of "south hot-north cold" that gradually decreased from southwest to northeast [53,54], and later evolved into an "east-west coexistence" pattern [55], mostly concentrated at high altitudes, undulating terrain, fragmented surfaces, near the middle and upper reaches of rivers, far from urban centers and major grain-producing areas, with low transportation access and less economically developed agroforestry areas [53,56,57]. Yangtze River, Pearl River, and southeastern rivers are considered as the main areas of traditional village distribution [58], and the proposal of constructing a conservation system scheme in terms of policy guidance-inputintegration-category-collaboration [59].…”
Section: Introductionmentioning
confidence: 99%
“…These studies always involve a large sample size, which may reach thousands of villages, and quantify the spatial relationship between villages and rivers using GIS spatial statistics. Gao et al (2021) studied 1222 Chinese traditional villages in eight provinces the Yellow River flows through. The results show that the overall spatial distribution of the traditional villages displays great regional differentiation affected both by natural factors and socioeconomic factors.…”
Section: Water Adaptability Of Rural Settlements In the Basinmentioning
confidence: 99%
“…(Li et al, 2017b). However, intensive erosion still occurs on sparsely vegetated steep slopes during intensive rainfall events (Gao et al, 2020).…”
Section: Study Sitementioning
confidence: 99%